Cerebral complications in diabetic ketoacidosis - Hatun, Sükrü; Cizmecioğlu, Filiz; Toprak, Demet (The Turkish Journal of Pediatrics, 2005)
Although much is known about diabetic ketoacidosis (DKA) and its treatment, the pathology of cerebral complications in patients who develop ketoacidosis is not yet well understood. In this article, we discuss the cerebral complications due to DKA by presenting two cases who were admitted with severe DKA and who both developed early and severe neurological complications.